Unravelling the stratigraphy and sedimentation history of the uppermost Cretaceous to Eocene sediments of the Kuching Zone in West Sarawak (Malaysia), Borneo. (July 2018) - Breitfeld, H. Tim; Hall, Robert; Galin, Thomson; BouDagher-Fadel, Marcelle K.
Graphical abstract: Highlights: Fore-arc basin sedimentation (Pedawan Formation) terminated in the Santonian. Sedimentation resumes with the fluvio-deltaic Kayan Group in the Maastrichtian. Unconformably overlain by the Middle to Late Eocene fluvio-marine Ketungau Group. Paleocurrent measurements indicate sources from the south (Schwaner Mountains area) Additional sources include West Borneo, Sundaland and Mesozoic melanges in the east. Abstract: The Kuching Zone in West Sarawak consists of two different sedimentary basins, the Kayan and Ketungau Basins. The sedimentary successions in the basins are part of the Kuching Supergroup that extends into Kalimantan. The uppermost Cretaceous (Maastrichtian) to Lower Eocene Kayan Group forms the sedimentary deposits directly above a major unconformity, the Pedawan Unconformity, which marks the cessation of subduction-related magmatism beneath SW Borneo and the Schwaner Mountains, due to termination of the Paleo-Pacific subduction. The successions consist of the Kayan and Penrissen Sandstones and are dominated by fluvial channels, alluvial fans and floodplain deposits with some deltaic to tidally-influenced sections in the Kayan Sandstone. In the late Early or early Middle Eocene, sedimentation in this basin ceased and a new basin, the Ketungau Basin, developed to the east. This change is marked by the Kayan Unconformity. Sedimentation resumed in the Middle Eocene (Lutetian) with the marginal marine, tidal to deltaic Ngili Sandstone and Silantek Formation. Upsequence, the Silantek Formation is dominated by floodplain and subsidiary fluvial deposits. The Bako-Mintu Sandstone, a potential lateral equivalent of the Silantek Formation, is formed of major fluvial channels. The top of the Ketungau Group in West Sarawak is formed by the fluvially-dominated Tutoop Sandstone. This shows a transition of the Ketungau Group in time towards terrestrial/fluvially-dominated deposits. Paleocurrent measurements show river systems were complex, but reveal a dominant southern source. This suggests uplift of southern Borneo initiated in the region of the present-day Schwaner Mountains from the latest Cretaceous onwards. Additional sources were local sources in the West Borneo province, Mesozoic melanges to the east and potentially the Malay Peninsula. The Ketungau Group also includes reworked deposits of the Kayan Group. The sediments of the Kuching Supergroup are predominantly horizontal or dip with low angles and form large open synclines. Steep dips are usually restricted to faults, such as the Lupar Line.